3D Patterning of Si by Contact Etching With Nanoporous Metals - Bastide, Stéphane; Torralba, Encarnacion; Halbwax, Mathieu; Le Gall, Sylvain; Mpogui, Elias; Cachet-Vivier, Christine; Magnin, Vincent; Harari, Joseph; Yarekha, Dmitri; Vilcot, Jean-Pierre (Frontiers in Chemistry, 2019)
Nanoporous gold and platinum electrodes are used to pattern n-type silicon by contact etching at the macroscopic scale. This type of electrode has the advantage of forming nanocontacts between silicon, the metal and the electrolyte as in classical metal assisted chemical etching while ensuring electrolyte transport to and from the interface through the electrode. Nanoporous gold electrodes with two types of nanostructures, fine and coarse (average ligament widths of ~30 and 100 nm, respectively) have been elaborated and tested. Patterns consisting in networks of square-based pyramids (10 x 10 µm2 base x 7 µm height) and U-shaped lines (2, 5 and 10 µm width x 10 µm height x 4 µm interspacing) are imprinted by both electrochemical and chemical (HF-H2O2) contact etching. A complete pattern transfer of pyramids is achieved with coarse nanoporous gold in both contact etching modes, at a rate of ~0.35 µm min-1. Under the same etching conditions, U-shaped line were only partially imprinted. The surface state after imprinting presents various defects such as craters pores or porous silicon. Small walls are sometimes obtained due to imprinting of the details of the coarse gold nanostructure. We establish that np-Au electrodes can be turned into “np-Pt” electrodes by simply sputtering a thin platinum layer (5 nm) on the etching (catalytic) side of the electrode. Imprinting with np Au/Pt slightly improves the pattern transfer resolution. 2D numerical simulations of the valence band modulation at the Au/Si/electrolyte interfaces are carried out to explain the localized aspect of contact etching of n-type silicon with gold and platinum and the different surface state obtained after patterning. They show that n-type silicon in contact with gold or platinum is in inversion regime, with holes under the metal (within 3 nm). Etching under moderate anodic polarization corresponds to a quasi 2D hole transfer over a few nanometers in the inversion layer between adjacent metal and electrolyte contacts and is therefore very localized around metal contacts.